STUDI KELAYAKAN PROYEK REVITALISASI PASAR TRADISIONAL KRANJI BARU KOTA BEKASI PROVINSI JAWA BARAT - Lalu Solihin (JURNAL LENTERA BISNIS, 2015)
The growth of modern markets in Bekasi municipality was growing rapidly, but the existence of traditional markets is maintained. It is seen from the government policies that will revitalize the entire traditional market in this area. The purpose of this study is to analyse the feasibility of the economic aspects of the revitalization project of Kranji Baru market in Bekasi Municipality of West Java. The data show the total cost of investment for the project is 94.02 billion rupiah , while operating costs per year is 4.2 billion rupiah. Sources of income derived from the rental location and some regular retributions from each merchant. Total revenues from rental locations is 124.2 billion rupiah per 20 years, and the income of retributions collected from traders is 4.4 billion dollars per year. The results of the feasibility of using the NPV calculation is Rp.41.711.420.487 , IRR koefisien is 0.08 , and BC ratio koefisien is 1.07. From the results of these calculations can be concluded that the revitalization project Kranji Baru market of Bekasi municipality is feasibleKeywords: Feasibility Study , Traditional Market , Bekasi Mucipality